UJI AKTIVITAS ANTIBAKTERI EKSTRAK TUNGGAL DAN KOMBINASI DAUN NANGKA (Artocarpus heterophyllus) DENGAN DAUN LABU SIAM (Sechium edule (Jacq.) Swartz) TERHADAP DAYA HAMBAT Salmonella typhi - Yuniar Ambarwati; Faisal; Majida Ramadhan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Antibiotic resistance in Salmonella typhi has become a major problem in Indonesia, where typhoid fever remains common and the effectiveness of antibiotics is diminishing due to this resistance. Jackfruit leaves (Artocarpus heterophyllus) are a plant source of active compounds such as flavonoids, tannins, and saponins. Meanwhile, chayote (Sechium edule) leaf extract contains active compounds such as saponins and tannins. This study aimed to determine the antibacterial activity of a combination of chayote leaf and fruit extracts against Salmonella typhi, as well as to identify the most optimal concentration. The study employed an experimental design using a completely randomized design (CRD). The treatments consisted of a positive control (chloramphenicol) and a negative control (distilled water), single extracts of jackfruit and chayote leaves at concentrations of 25%, 50%, 75%, and 100%, and combinations of jackfruit and chayote extracts at ratios of 1:1, 2:1, and 1:2, with each treatment repeated three times. Data for the single jackfruit and chayote extracts, as well as the N:LS (1:1) combination, were analyzed using the Kruskal-Wallis, while the N:LS (1:2) and N:LS (2:1) combinations were analyzed using one-way ANOVA. The results of the study showed that all treatments exhibited antibacterial activity ranging from moderate to strong, and the extract combinations demonstrated higher inhibitory activity compared to the single extracts, with the combination of jackfruit leaves and chayote leaves